Free‐breathing cine imaging with motion‐corrected reconstruction at 3T using SPiral Acquisition with Respiratory correction and Cardiac Self‐gating (SPARCS). Issue 2 (21st April 2019) - Zhou, Ruixi; Yang, Yang; Mathew, Roshin C.; Mugler, John P.; Weller, Daniel S.; Kramer, Christopher M.; Ahmed, Abdul Haseeb; Jacob, Mathews; Salerno, Michael
Abstract : Purpose: To develop a continuous‐acquisition cardiac self‐gated spiral pulse sequence and a respiratory motion‐compensated reconstruction strategy for free‐breathing cine imaging. Methods: Cine data were acquired continuously on a 3T scanner for 8 seconds per slice without ECG gating or breath‐holding, using a golden‐angle gradient echo spiral pulse sequence. Cardiac motion information was extracted by applying principal component analysis on the gridded 8 × 8 k‐space center data. Respiratory motion was corrected by rigid registration on each heartbeat. Images were reconstructed using a low‐rank and sparse (L+S) technique. This strategy was evaluated in 37 healthy subjects and 8 subjects undergoing clinical cardiac MR studies. Image quality was scored (1–5 scale) in a blinded fashion by 2 experienced cardiologists. In 13 subjects with whole‐heart coverage, left ventricular ejection fraction (LVEF) from SPiral Acquisition with Respiratory correction and Cardiac Self‐gating (SPARCS) was compared to that from a standard ECG‐gated breath‐hold balanced steady‐state free precession (bSSFP) cine sequence. Results: The self‐gated signal was successfully extracted in all cases and demonstrated close agreement with the acquired ECG signal (mean bias, –0.22 ms). The mean image score across all subjects was 4.0 for reconstruction using the L+S model. There was good agreement between the LVEF derived from SPARCS and the gold‐standard bSSFP technique. Conclusion: SPARCS successfully images cardiac function without the need for ECG gating or breath‐holding. With an 8‐second data acquisition per slice, whole‐heart cine images with clinically acceptable spatial and temporal resolution and image quality can be acquired in <90 seconds of free‐breathing acquisition.